VLF Sensors for Lightning Research. (2016) - Mochalov, V.; Sannikov, D.; Karimov, R.; Shevtsov, B.; Drugin, G.; Cherneva, N.; Mochalova, A.; Lichtenberger, J.; Argunov, V.
Abstract: The lightning localization task is very interested for the meteorologist organizations, airlines, networks operators, military and etc. The electromagnetic properties of lightning can be measured using VLF sensor. The paper deals with some hardware and software of VLF sensors used in IKIR FEB RAS.